Towards a Penal Law for Religious? (II/3) Consecrated Life in the Light of Pope Francis’s 2021 Reform of Book VI of the CIC: Part II. Special Considerations (3): the Evangelical Counsel of Poverty as the Object of Penal Protection - Skonieczny, Piotr (Prawo Kanoniczne, 2025)
The author analyses the discipline of religious life from the perspective of penal law in the light of Pope Francis’s recent reform of Book VI CIC/21 of 2021. The author asks whether it is possible to speak of a penal law for religious after the reform of Book VI of 2021. The fourth article is devoted to specific issues, in particular the penal protection of the evangelical counsel of poverty. According to the author, the reform of Book VI CIC/21, in particular the regulation of delicts in re oeconomica, called by the author ‘delicts contra VII Decalogi praeceptum’ (I.1., III.1.1.), has indirectly strengthened the penal protection of the vow of poverty in the consecrated life, with the concomitant protection of this evangelical counsel in disciplinary terms (I.2., I.3., “Conclusioni parziali III”: Partial conclusions III). The author analyses the subjective scope of application of the new expiatory penalty of the fine in can. 1336 § 2, no. 2 CIC/21 (II.). According to the author, the fine penalty is not possible in the case of religious who fully renounce their property (II.1.). On the contrary, these religious should be deprived of their so-called peculium by disciplinary and not penal means (II.2.). Analysing the anti-juridical element of the new contra VII delicts in the context of consecrated life, the author states that the ‘subtrahere’ in canon 1376 § 1, no. 1 CIC/21 also includes the misappropriation of ecclesiastical property, including religious property (III.1.2.). On the other hand, the new canon 1393 § 2 CIC/21 provides a reservation clause whereby it applies only when other delicts in re oeconomica cannot be applied to contra VII cases (III.1.3.). As far as culpability is concerned, it will not be possible to invoke ignorance on the part of the consecrated person of the rules on the management of ecclesiastical property (III.2.). Finally, as regards the legal element, the author criticises the penalties provided for in canon 1376 CIC/21, which he considers ineffective against consecrated persons (III.3.). In conclusion, according to the author, the reforms introduced by Pope Francis, particularly in Book VI CIC/21, have not changed the model of protection of the vow of poverty in consecrated life already present in the 1983 Code of St John Paul II. According to the general principle of a double responsibility, it is still rightly a matter of primarily disciplinary responsibility, followed by penal responsibility. On the other hand, because of the diversity of the content of the vow of poverty in the various Institutes, it is not possible to create a uniform penal law for religious that protects the evangelical counsel commented on (“Conclusioni parziali III”: Partial conclusions III).